Monitoring of perioperative tissue perfusion and impact on patient outcomes - Bin Li; Yuchen Dai; Wenlan Cai; Menghan Sun; Jie Sun (Journal of Cardiothoracic Surgery)
Abstract Monitoring perioperative tissue perfusion is crucial in clinical anesthesia to protect organs and ensure patient safety. Indicators like hemodynamic parameters, tissue metabolism, and microcirculation markers are used for assessment. Studies show intraoperative hypotension negatively impacts outcomes, though blood pressure alone may not reflect tissue perfusion accurately. Cardiac output is a more direct measure, with adequate levels generally indicating good perfusion. However, some conditions cause adequate cardiac output but inadequate perfusion. Non-quantitative markers like skin color and temperature, and quantitative indicators like tissue oxygen saturation and laser Doppler flowmetry, help assess microcirculation but can’t fully evaluate systemic perfusion. Near-Infrared Spectroscopy (NIRS) monitors tissue oxygen metabolism, reflecting oxygen supply and consumption balance. Central venous oxygen saturation offers a better systemic overview but may not always indicate good perfusion, especially in sepsis. Lactic acid levels closely correlate with tissue perfusion and outcomes, with dynamic changes being more indicative than single measurements. Effective monitoring requires evaluating both macro- and microcirculation states and systemic metabolic levels to ensure optimal outcomes. Combining these measures provides a more accurate assessment of tissue perfusion and patient prognosis.